Sistem Informasi Manajemen Arsip Pada Komisi Pemilihan Umum Provinsi Jambi - Isto’in Choirul, Galang; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2023)
The analysis and design of the archives management information system at KPU Jambi Province is a research that produces a design of a records management system that is expected to answer the problems that arise at this time, namely the process of managing records that still use manual methods and the absence of well- managed archival records. This research uses the prototype method with the UML (Unified Modeling Language) approach. This research produces a prototype that can provide an overview of the design of the archives management information system and the UML (Unified Modeling Language) approach as a tool that can facilitate the developer later in making the information system. With this the resulting prototype could be the first step for the Jambi Province KPU in managing records better.